Prevalence and Molecular Characterization of Mycoplasma ovis in Selected Free-Ranging Brazilian Deer Populations - Grazziotin, Ana Laura; Barbanti Duarte, Jose Mauricio; Juan Szabo, Matias Pablo; Santos, Andrea Pires; Sa Guimaraes, Ana Marcia; Mohamed, Ahmed; da Costa Vieira, Rafael Felipe; de Barros Filho, Ivan Roque; Biondo, Alexander Welker; Messick, Joanne Belle (Wildlife Disease Assoc, Inc, 2011)
Mycoplasma ovis is a hemoplasma that may cause anemia and mortality in small ruminants. Our aim was to determine whether M. ovis infects populations of free-ranging deer in Brazil. Bully coat samples from 64 Blastocerus dichotomus from Porto Primavera, 18 Ozotocerus bezoarticus from Pantanal, and 21 O. bezoarticus from Emas National Park were tested. Using a M. ovis PCR protocol to amplify extracted DNA, 46/64 (72%) of deer froth Porto Primavera, 10/18 (56%) from Pantanal, and 4/21 (19%) from Emas National Park were positive, giving an overall positive rate of 58% for hemoplasma in these wild deer. Sequencing and phylogenetic analysis of the 168 rRNA gene revealed 3 genetically distinct hemoplasmas including M. ovis, 'Candidatus Mycoplasma erythrocervae', and a hemoplasma most closely related to M. ovis. Phylogenetic analysis of the 23S rRNA gene from selected sequences confirmed these relationships.
Keywords: Blastocerus dichotomus; deer; hemoplasma; hemotropic mycoplasma; molecular characterization; Mycoplasma ovis; Ozotocerus bezoarticus; prevalence